2017
DOI: 10.1016/j.jss.2017.05.115
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative thrombelastography maximum amplitude predicts massive transfusion in liver transplantation

Abstract: Introduction Massive transfusion (MT) is frequently required during liver transplantation. Risk stratification of transplant patients at risk for MT is an appealing concept, but remains poorly developed. Thrombelastography (TEG) has recently been shown to reduce mortality when employed for trauma resuscitation. We hypothesize that preoperative TEG can be used to risk stratify patients for massive transfusion. Material and Methods Liver transplant patients had blood drawn prior to surgical incision and assaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
1
27
0
1
Order By: Relevance
“…Many studies have shown that TEG has detected hypercoagulation in the clinical setting. However, there is no consensus on the evaluation of the results due to differences in the types of operations and the methodologies applied, and the results of the studies are contradictory (6,7,(20)(21)(22). Dai et al (7) examined 10 studies that aimed at predicting postoperative thromboembolic events with TEG, and, as a result, they stated that although TEG is reported to be beneficial, all studies reported differences in methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that TEG has detected hypercoagulation in the clinical setting. However, there is no consensus on the evaluation of the results due to differences in the types of operations and the methodologies applied, and the results of the studies are contradictory (6,7,(20)(21)(22). Dai et al (7) examined 10 studies that aimed at predicting postoperative thromboembolic events with TEG, and, as a result, they stated that although TEG is reported to be beneficial, all studies reported differences in methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Indeed, in a single-centre study, maximum amplitude less than 47 mm on TEG predicted the need for MT in liver transplantation. [ 26 ] In our centre, FFP and other blood product transfusions were guided by TEG in the presence of clinical oozing. On no occasion was FFP transfused as a fixed ratio with PRBC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, preoperative values of TEG (low MA) have been shown to predict need for massive transfusion during liver transplantation. 18 Significant postperfusion bleeding from hyperfibrinolysis may occur during liver transplantation, and both ROTEM and TEG can assist in recognition and management of this challenging physiology. [19][20][21] Hypercoagulability is also of concern during liver transplantation, and thrombotic events can be catastrophic.…”
Section: Teg In Patients With Cirrhosis Undergoing Liver Transplantationmentioning
confidence: 99%